Pendampingan UMKM Kue Kering Uti Mama dalam Permasalahan Pemasaran dan Pencatatan Keuangan - Freyanissa Aksanti Kemaputri; Adelia Najla Rianty; Kerenhapukh Oktaria Viliany Siagian; Nabiel Isra Hidayat; Jeremy Bonauli Simamora; Aufaa Ahmad Shine Priyanka; Tri Siwi Agustina; Dunga Dwi Barinta (INDO PUBLISHING, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving Indonesia's economy through income generation, job creation, and improved community welfare. This assistance program aims to help Uti Mama, a dry cake business, address problems in marketing and financial record-keeping. The methods used include interviews and observations with the business owner, followed by guided implementation of solutions. The proposed solutions include establishing WhatsApp Business as a digital marketing channel, adding a location pin on Google Maps, and introducing a financial record-keeping system. Results show that WhatsApp Business and the Google Maps location pin had the most significant impact, making it easier for customers to find, contact, and order directly from the business. The owner's positive feedback confirms her ability to operate these tools independently for communication and marketing purposes. These solutions are expected to support the long-term sustainability and growth of Uti Mama's business.